The French Orientalist "Louis Jack Bresnier" and Contributions to the French Orientalist Movement in Algeria (1837-1869) - lecheheb, samir; abdelkamel, djouiba (The Algerian Historical Journal, 2026)
This paper seeks to shine light on a pioneer in orientalist studies in Algeria, the French orientalist and Arabist "Louis Jack Bresnier", the creator of the first Chair of the Arabic Language in Algeria. Louis Jack Bresnier is credited with reviving Arabic studies in Algeria, following a recommendation from his teacher, "Sylvester de Sacy", Since Bresnier arrival in Algeria in 1837, he paid rampt attention to Arabic studies and strived to establish a Chair of the Arabic Language in January 1837, This endeavor consists Bresnier sole mission, in which he engaged actively to achieve the colonial administration goals for promoting Arabic among Europeans. During his more-than-fifty-year linguistic career in Algerian, Bresnier wrote several books, and studies on teaching Arabic. For the sake of this project’s success, Bresnier spent more than half of his life in Algeria, until his death in 1869.